Global campaigning initiatives for socio-economic development - Carvalho, Luísa Cagica 1970-; Madeira, Maria José 1963- (IGI Global, 2019)
"This book focuses on the role and contribution of global campaigns, in accelerating economic growth with a multiplier effect on the national income by inviting global participation in all the sectors of socio economic development"...
Keywords: Economic development -- Developing countries; Economic development -- Developing countries -- International cooperation